2022
DOI: 10.3389/fpsyg.2022.778468
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Motor Imagery and Self-Talk on Service Performance in Skilled Tennis Players

Abstract: This research aim to investigate the effects of motor imagery (MI), focused on the trajectory of the ball and the target area, and self-talk (motivational function) before the actual strike on the performance of the service in skilled tennis players. Thirty-three participants (6 females and 27 males, Mage = 15.9 years), competing in regional to national competitions, were randomly divided into three groups: Control, MI, and MI + self-talk. They performed a pre-test (25 first service), 20 acquisition sessions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…RoB-2 assessments were conducted on four RCTs [ 23 , 40 , 41 , 42 ], while ROBINS-I assessments were employed for five non-RCTs [ 22 , 24 , 25 , 43 , 44 ]. Out of these trials, only three displayed a low risk of bias, while six demonstrated an overall moderate risk of bias or some concerns, as illustrated in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RoB-2 assessments were conducted on four RCTs [ 23 , 40 , 41 , 42 ], while ROBINS-I assessments were employed for five non-RCTs [ 22 , 24 , 25 , 43 , 44 ]. Out of these trials, only three displayed a low risk of bias, while six demonstrated an overall moderate risk of bias or some concerns, as illustrated in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these RCTs, only one reported their randomization sequence generation method [ 23 ]. In contrast, the randomized procedures in the remaining three papers were not comprehensively described [ 40 , 41 , 42 ]. A visual depiction of the findings of ROBINS-I assessments is shown in Figure 2 B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and MI was more effective than either S.T. or MI in reducing state anxiety and increasing the S.C. and archery performance of 45 Malaysian national archery athletes [ 59 ]; it was also found that the combination of motivational-ST and MI, performed before serving, was beneficial for 33 skilled tennis players [ 60 ]. It was found that the MI intervention and the combination of MI and S.T.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicate that strategies aimed at restoring service performance in professional tennis players during and after the COVID-19 pandemic are urgently required, especially in male and lower-ranked players. The training strategies for improving service performance that have less pandemic-related restrictions may be useful for players and their team, for example, mental training programs, 4 including video modeling training, 5 perceptual-cognitive skills training, 6 imagery training, 7 and deepening the understanding of useful strategies for improving service performance during the match, such as pacing strategies. 8 The present study is the first to use large-scale population data to examine the impact of temporary tours withdrawal on the performance of professional tennis players.…”
mentioning
confidence: 99%